2008
DOI: 10.1364/oe.16.002226
|View full text |Cite
|
Sign up to set email alerts
|

Broadly tunable ultraviolet miniature cerium-doped LiLuF lasers

Abstract: Ultraviolet (UV) miniature cerium fluoride lasers have been demonstrated using a low cost, frequency-quadrupled microchip Nd:YAG pump laser. The use of miniature laser cavities was shown to significantly improve the laser performance in the low pump power region. We have achieved slope efficiencies up to 70% and pump thresholds as low as 100 nJ. Continuous tuning from 306 nm to 338 nm was achieved using a Brewster angle prism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A frequency-quadrupled Nd:YVO 4 (and Nd:YAG) laser at 266 nm can excite most lanthanide; however, such a deep UV is too destructive to the biology system and requires the optics to function at that short wavelength. Although recent solid-state laser research has demonstrated pulsed laser sources for this wavelength band (27,28), they are far more expensive compared with the light emitting diode (LED) sources (10,29). Another problem arising from this bandwidth is that the routine microscopes have too low transmission to deliver the power to the specimen, since most microscopy objectives and slide cover slips have the cuton edge from 330 to 340 nm.…”
mentioning
confidence: 99%
“…A frequency-quadrupled Nd:YVO 4 (and Nd:YAG) laser at 266 nm can excite most lanthanide; however, such a deep UV is too destructive to the biology system and requires the optics to function at that short wavelength. Although recent solid-state laser research has demonstrated pulsed laser sources for this wavelength band (27,28), they are far more expensive compared with the light emitting diode (LED) sources (10,29). Another problem arising from this bandwidth is that the routine microscopes have too low transmission to deliver the power to the specimen, since most microscopy objectives and slide cover slips have the cuton edge from 330 to 340 nm.…”
mentioning
confidence: 99%